2016
DOI: 10.29173/iq904
|View full text |Cite
|
Sign up to set email alerts
|

Research Data Repositories: Review of Current Features, Gap Analysis, and Recommendations for Minimum Requirements

Abstract: Research Data Repositories: Review of Current Features, Gap Analysis, and Recommendations for Minimum Requirements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 9 publications
0
33
0
5
Order By: Relevance
“…Successfully archiving and sharing data from research and scholarly work is increasingly seen as critical to the practice of science, and adherence to interoperability standards ensures that research results are available to users who could make use of the data (Austin et al . ). Such standards have recently been deemed necessary in ensuring that data from research can be translated into “actionable knowledge” and have also been prioritized by US federal agencies (such as NOAA and NASA) in the domains of environmental and climate‐change studies (Hesse et al .…”
Section: Community‐based Observingmentioning
confidence: 97%
See 1 more Smart Citation
“…Successfully archiving and sharing data from research and scholarly work is increasingly seen as critical to the practice of science, and adherence to interoperability standards ensures that research results are available to users who could make use of the data (Austin et al . ). Such standards have recently been deemed necessary in ensuring that data from research can be translated into “actionable knowledge” and have also been prioritized by US federal agencies (such as NOAA and NASA) in the domains of environmental and climate‐change studies (Hesse et al .…”
Section: Community‐based Observingmentioning
confidence: 97%
“…Development of data interoperability standards has been key in merging independent biophysical observing platforms and efforts (such as those relating to ocean acidification, circulation, and CO 2 enrichment) into integrated observing networks that are able to provide comprehensive and widely used data (Garcia et al 2015). Successfully archiving and sharing data from research and scholarly work is increasingly seen as critical to the practice of science, and adherence to interoperability standards ensures that research results are available to users who could make use of the data (Austin et al 2015). Such standards have recently been deemed necessary in ensuring that data from research can be translated into "actionable knowledge" and have also been prioritized by US federal agencies (such as NOAA and NASA) in the domains of environmental and climatechange studies (Hesse et al 2015;Schaefer et al 2015).…”
Section: How Are Data Interoperability and Quality Ensured?mentioning
confidence: 99%
“…Retrieved November 11, 2015, from http://www-pcmdi.llnl.gov/projects/cmip/. 20 Approved by the data journal. cation as represented in the 'Additional elements' of Fig.…”
Section: Detailed Workflows and Dependenciesmentioning
confidence: 99%
“…An important consideration for our study is that support for 'normal' curation falls short of best practice standards. For example, having conducted a survey of 32 international online data platforms [20], the Standards & Interoperability Committee of Research Data Canada (RDC) 9 concluded that there is still a great deal of work to be done to ensure that online data platforms meet minimum standards for reliable curation and sharing of data, and developed guidelines for the deposit and preservation aspects of publishing research data.…”
Section: Introductionmentioning
confidence: 99%
“…These studies focus on analyzing individual projects, applications, or conceptual ideas and specific contexts such as Linked Data and Open Data. There are other approaches to publish data on the Web, such as Big Data [13,20] and Web Semantic Sensor Data [107], and there are specific communities that publish and consume data on the Web without following Linked Data or Open Data principles, such as research data communities [9]. A systematic and holistic review is necessary in order to provide further insights on the current state of research related to publish data on the Web as well as the overall development of the topic, which can form the basis for shaping future works.…”
Section: Related Workmentioning
confidence: 99%